NEW RESULTS ON DELIAS FROM THE CENTRAL YOUNTAIN RANGE OF IRIAN JAY A (LEPIDOPTERA: PIERIDAE) - Fred Gerrits; Henk van Mastrigt (Treubia, 1992)
Five new species and four new subspecies of Delias are described fromthe central mountain ranges of Irian Jaya, Indonesia. D. luctuosa gottsisubsp. n. and D. callista callipulchra subsp. n. from Tembagapura (13708' E.), the south side of the Puncak Jaya, former Carstensz Peak, D.pseudomarguerita sp. n. from Homeyo (136053' E.), D. virgo sp. n.,D.neeltje sp. n. and D. phippsi mulia subsp. n. from the middle ranges(137030'-13SoE.), D. hemianops sp. n. from Abmisibil in the StarMountains (1410 E)., D. langda langda sp. n. from langda (1400 E.) andD. langda watlangku subsp. n. from the northeastern side of the BaliemValley (1390 E.).